Evaluation of cryopreservation methods for in vitro produced bovine embryos - Nedambale, Tshimangadzo Lucky (University of the Free State, 1999)
The objective of this study was to evaluate four cryopreservation techniques for in vitro produced bovine embryos, and to select the best method for practical application. The cryopreservation methods investigated were three vitrification methods and a slow freezing method. This study was done at the ARC-Animal Improvernent Institute in conjunction with the University of the Orange Free State (Department of Animal Science). Embryos were obtained by the IVM, IVF and IVC of bovine follicular oocytes. A total of 136 early blastocysts, blastocysts and expanded blastocysts were randomly assigned to four different treatment groups. In the conventional slow freezing method, the IVP bovine embryos were first held in ViGro™Holdingplus medium before being transferred to 1.5M ViGro™EG Freezeplus medium (TMT 4). In this technique, the IVP embryos were loaded into 0.25ml straws. The straws containing the embryos were immediately placed into a programmable freezer (CL-863 cryo-chamber) at -6°C. Straws were seeded after a 5 minutes equilibration period. Embryos were initially cooled from -6 "C to -30°C at a rate of 0.3 °C/min. Thereafter, from -30°C to -33°C the rate was changed to 0.1 °C/min. After the target temperature was reached, straws were immediately transferred to liquid nitrogen. Vitrification of IVP bovine embryos was performed according to the following procedures: Embryos were initially placed in 10% EO in ViGro™Holdingplus medium for 5 minutes (Equilibration I), thereafter in 40% EO + 0.3M trehalose in ViOro ™Holdingplus medium for 5 minutes (Equilibration 11), both at room temperature. Embryos were then transferred to vitrification solutions, containing 40% EO (TMT 1); 40% EG + 0.3M trehalose (TMT 2); 40% EG + 0.3M trehalose + 20% PVP (TMT 3) in ViGro TM Holdingplus. Embryos were then loaded into 0.25ml straws, and plunged directly into liquid nitrogen (LN2). The straws were vertically stored in liquid nitrogen (- 196°C) until thawing and evaluation took place. Thawing of embryos within the straws was carried out in a water bath (32 DC). Each straw was placed in a water bath for 30 seconds. The straws were dried, cut and the contents transferred to ViGro ™Holdingplus medium. Recovered embryos were washed twice in fresh ViGro™I-Ioldingplus, and embryos were morphological examined for their viability under a stereo microscope. The viable embryos were cultured in IVC media. Embryo survival was recorded immediately after thawing, 24 hours and 48 hours post-thawing by monitoring the re-expansion of the blastocoel and expansion of the blastocyst. Statistically, there was a significant (P<0.05) difference in survival rate between embryos frozen in TMT 3 (77%), compared to those frozen in TMT 2 (41%), immediately after thawing. There was no significant difference in embryo survival rate for the other treatment groups. At 24 hours post-thawing, there was a significant (P<0.05) difference in survival rate between embryos frozen in TMT 3 (60%), compared to those frozen in TMT 1 (26%). There was also a significant (P<0.05) higher survival rate for embryos frozen in TMT 3 (60%), compared to those frozen in TMT 2 (21%). At 48 hours post-thawing, however, there was no significant difference in survival rate for embryos frozen in all the treatment groups. TMT 3 had the highest survival rates of embryos (37%). The generalized linear model (Bonferroni multiple comparison test) was used to test and predict the embryo survival rate between the treatment groups. The predicted (theoretical) embryo survival rate correlated highly and significantly (P<0.05) higher with the survival rate of embryos frozen in TMT 3. Embryos Frozen in TMT 3 were also predicted to be more likely to survive, compared to the other treatment groups. The results clearly indicate the beneficiary effect of this vitrification method (TMT 3). Vitrification is simple and more cost effective, compared to the slow freezing method (TMT 4), which is time consuming and expensive. Although there was no significant difference 48 hours ostthawing, TMT 3 could be recommended as the method for cryopreservation of IVP bovine embryos. The addition of 0.3M trehalose with 40% EO in the ViGro™Holdingplus medium decreased the survival rates of the IVP bovine embryos. Embryos frozen and thawed in 40% EO in ViGro™Holdingplus had higher survival rates, compared to those frozen/thawed in TMT 2, from immediately after thawing, to 48 hours post-thawing. Perhaps the addition of trehalose in the solution (ViGro™Holdingplus), already containing non-permeating agent (sucrose), increased the concentration of non-permeating agent in the freezing solution. High concentrations of non-permeating agent may be detrimental or toxic to the embryos. The presence of 20% PVP with 0.3M trehalose and 40% EO dramatically increased the survival rate of IVP bovine embryos. The PVP plays some kind of protective role during the freezing and thawing processes. Although the mechanism of protection is not clear, it may be that it prevents water from entering the cells during vitrification and thawing, which in turn prevents intracellular ice formation. Intracellular ice formation is lethal to embryos during thawing. It can be concluded that the combination of 40 % EO + 0.3M trehalose + 20% pyp (TMT 3), used as a vitrification solution, be recommended as suitable method for cryopreservation of IVP bovine embryos. It gave the highest embryo survival rate from immediately after thawing to 48 hours post-thawing. The advantage of this vitrification technique is that it is simple, quick and inexpensive. Additional research is needed to develop an effective cryopreservation method that will reduce the sensitivity problem of in vitro produced embryos. In vitro produced embryos contain lipids that cause them to be more sensitive to freezing, compared to those produced in vivo. The ability of vitrified in vitro produced bovine embryos still needs to be evaluated for their development in utero, in controlled embryo transfer programs.

Die doel van die studie was om vier kriopreserverings tegnieke vir in vitro geproduseerde beesembrio's te evalueer en die die beste metode te selekteer vir praktiese toepassing. Die kriopreserveringsmetodes ondersoek, het bestaan drie vitrifikasiernetodes en 'n stadige stapsgewyse metode. Die studie IS uitgevoer by die LNR Diereverbeteringsinstituut in samewerking met die Universiteit van die Oranje Vrystaat (Departement Veekunde). Embrios is verkry deur IVM, IVB en IVK van follikulêre beesoosiete. 'n Totaal van 136 vroeë blastosiste, blastosiste en laat blastosiste was ewekansig toegedeel tot die vier behandelingsgroepe. In die konvensionele stapsgewyse bevriesingsmetode is die embrios in 'n Vigro TM houmedium geplaas en daarna in 1.5 M Vigro TM EG freezeplus medium oorgeplaas - behandeling 4 (TMT4). Met die tegniek is die embrios in 0.25 ml strooitjies gelaai en direk in 'n programmeerbare bevriesingsapparaat (CL 863 eryoehamber) by 'n temparatuur van -6°C. geplaas Na 'n ekwilibrasieperiode van 5 minute is die strooitjies geinduseer vir vinnige ysvorming. Embrios is inisieel afgekoel teen' n tempo van 0.3 "Czminuut tot 'n temparatuur van -30°C, daarna van -30 °C tot en met -33°C teen 'n tempo van 0.1 "Czminuut. Nadat die teikentemperatuur bereik is, is die strooitjies direk in vloeibare stikstof gedompel. Strooitjies is vertikaal gestoor in vloeibare stikstof (-196 QC) tot en met ontdooiing en evaluasie. Vitrifasie van embrios is gedoen volgens die volgende prosedures. Embrios is aanvanklik geplaas in 'n 10% EG in Vigro TM houmedium vir 'n periode van 5 minute (ekwilibrasie J), daarna in 40% EG + 0.3 M trehalose in Vigro TM houmedium vir 5 minute (ekwilibrasie II). Beide stappe is by kamertemperatuur uitgevoer. Embrios is daarna oorgeplaas na vitrifikasie oplossings bevattende 40% EG (TMTI); 40% EG + 0.3 TM M trehalose (TMT2); 40% EG + 0.3 M trehalose + 20% pyp (TMT3) in ViGro Houmedium. Embrios is gelaai in 0.25 strooitjies en direk in vloeibare stikstof geplaas. Embrios is vertikaal in vloeibare stikstof (-196°C) geberg, totdat hulontdooi en geëvalueer is. Ontdooiing van embrios is uitgevoer in 'n waterbad (32°C). Elke strooitjie is in die bad water geplaas vir 30 sekondes waarna dit afgedroog, geknip en die inhoud oorgeplaas is na 2 ml ViGro TM Houmedium. Herwonne embrios is twee maal gewas in vars ViGro™ I-Ioumedium, waarna hul morfologies ondersoek is vir lewensvatbaarheid onder 'n stereomikroskoop. Die lewendige embrios is gekweek in lYK media en die embrio oorlewingstempo is vasgestel net na ontdooiing, 24 uur en 48. uur na ontdooiing deur die monitering van die her-uitsetting van die blastosoei en uitsetting van die blastosist. Statisties was daar 'n betekenisvolle (P<0.05) verskil, (onmiddellik na ontdooiing), in oorlewing tussen embrios gevries in TMT3 (77%), vergeleke met die gevries in TMT2 (41%). Geen betekenisvolle verskil in oorlewing is verkry tussen die ander groepe nie. By 24 uur na ontdooiing, was daar 'n betekenisvolle (P<0.05) verskil in oorlewingstempo tussen embrios in TMT3 (60%) en TMT 1 (26%). Daar was ook 'n betekenisvolle (P<0.05) hoër oorlewingstempo vir embrios na TMT3 behandeling (60%), vergeleke met daardie gevries III TMT2 (21(Yo). By 4g uur na untdouiing is daar egter geen betekenisvolle verskil in oorlewingstempo tussen die behandelingsgroepe gekry nie. TMT3 het die hougste oorlewing vir die IYP beesembrios getuun (37%). Die liniêre model (Bonferroni meervoudige vergelykingstoets) is gebruik om die oorlewing tussen behandelingsgroepe te evalueer en te voorspel. Die voorspelde (teoretiese) embrio oorlewingstempo het 'n hoë oorlewing vir embrios in TMT3 getoon. Embrios gevries in TMT3 behandeling, is ook voorspelom meer waarskynlik te oorleef, vergeleke met die ander behandelingsgroepe. Resultate toon 'n definitiewe voordeel ten opsigte van hierdie vitrifikasietegniek (TMT3). Yitrifikasie is 'n eenvoudige tegniek en nie so duur, vergeleke met die stapsgewyse bevriesingsmetode (TMT4), wat tydrowend en duur is. Alhoewel daar geen betekenisvolle verskil na 48 uur na-ontdooiing was nie, kan TMT3 aanbeveel word as die beste metode vir die kriobewaring van IVP beesembrios. Die byvoeging van 0.3M trehalose met 40% EG in die YiGro™ I-Ioumedium medium veroorsaak 'n afname in die oorlewing van IVP beesembrios. Embrios gevries en ontdooi in 40% EG in ViGro™ Houmedium. het hoër oorlewing getoon, vergeleke met embrios gevries in TMT2, onmiddellik na ontdooiing tot 48 uur na ontdooiing. Waarskynlik het die byvoeging van trehalose in die oplossing, wat reeds 'n nie-deurlaatbare middel (sukrose) bevat, die konsentrasie van nie-deurlaatbare middels in die bevriesingsmedium verhoog. Hoë konsentrasies nie-deurlaatbare middels kan nadelig oftoksies wees vir die embrios. Die teenwoordigheid van 20% PVP met 0,3M trehalose en 40% EG het die oorlewing van die IVP beesembrios dramaties verbeter. pyp speel "n beskermende rol tydens bevriesing en ontdooiing. Alhoewel die meganisme van beskerming nie duidelik is nie, mag dit wees dat dit die invloei van water in die sel verhoed tydens vitrifikasie en ontdooiing. So doendeword die vorming van intrasellulêre ys verhoed. Intrasellulêre ysvorming is fataal vir die oorlewing tot gevolg gehad van embrios tydens ontdooiing. Samevattend kan gesê word dat 40% EG + 0.3 M trehalose + 20% PVP (TMT 3) die aanbevole metode van kriobewaring van IVP beesembrios is. Dit het die hoogste oorlewing gegee van ontdooiing tot 48 uur na ontdooiing. Die voordeel van hierdie tegniek vitrifikasie is dat dit eenvoudig, vinnig en goedkoop is. Addisionele navorsing is egter nog nodig om 'n effektiewe kriopreserveringstegniek te ontwikkel wat die sensitiwiteit van in vitro geproduseerde embrios sal verlaag. In vitro geproduseerde embrios bevat meer lipiede as in vivo embrios wat 'n verhoogde sensitiwiteit vir bevriesing veroorsaak. Die vermoë van gevitrifiseerde in vitro embrios om in utero te ontwikkel moet nog III gekontroleerde embrio-oorplasings programmebepaal word.
Dissertation (M.Sc.Agric. (Animal Science))--University of the Free State, 1999
Keywords: IVEP; Bovine embryos; Vitrification; Conventional slow freezing; IVM; IVF; PVP; EG; Trehalose; Survival rate; Cattle -- Artificial insemination; Cattle -- Breeding